Identification of alterations in the nucleotide sequence of the chromatin remodeling gene PBRM1 in clear cell renal cell carcinoma patients - E. A. Klimentova; I. R. Gilyazova; A. A. Izmailov; I. M. Sultanov; M. A. Bermisheva; V. N. Pavlov; E. K. Khusnutdinova (Вавиловский журнал генетики и селекции)
Kidney cancer is a heterogeneous group of malignant tumors, the vast majority of which are renal cell carcinomas (RCC) of various morphological types, of which the most common is the clear cell renal cell carcinoma (ccRCC). Particular attention in the carcinogenesis of the ccRCC is given to a number of tumor suppressor genes located on the short arm of the third chromosome. One of these genes, which are inactivated in the case of ccRCC is the PBRM1 gene encoding the PBAF SWI/SNF subunit of the chromatin remodeling complex, BAF180. The PBRM1 gene is located on the short arm of the third chromosome in the 3p21 region near the von Hippel-Lindau gene (VHL), the mutation in which is the main event in the occurrence of ccRCC. The aim of our investigation is identification of changes in the nucleotide sequence of the PBRM1 tumor suppressor gene in patients with ccRCC. 210 pairs of DNA samples isolated from ccRCC tissue were studied. Analysis of changes in the nucleotide sequence of DNA was carried out by HRM analysis and direct sequencing. In the PBRM1 gene, two somatic mutations were found (c.233G>A (p.D45N) in exon 2, c.1675-1676delTC in exon 15) which were not described previously, and one known polymorphic variant rs17264436 (in exon 23). The frequency of detected mutations was 0.95 % of cases. Analysis of the allelic association for the polymorphic locus rs17264436 showed a statistically significant increase in the risk of developing advanced kidney cancer in carriers of allele rs17264436*A, which can be used in the development of prognostic marker panels. Perhaps the low frequency of mutations in the samples we studied is due to the fact that the inactivation of the PBRM1 gene takes place in other ways, and may also be due to the ethno-specificity of the studied group of patients.